(2t-5t)(t-1)=2

Simple and best practice solution for (2t-5t)(t-1)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2t-5t)(t-1)=2 equation:


Simplifying
(2t + -5t)(t + -1) = 2

Combine like terms: 2t + -5t = -3t
(-3t)(t + -1) = 2

Remove parenthesis around (-3t)
-3t(t + -1) = 2

Reorder the terms:
-3t(-1 + t) = 2
(-1 * -3t + t * -3t) = 2
(3t + -3t2) = 2

Solving
3t + -3t2 = 2

Solving for variable 't'.

Reorder the terms:
-2 + 3t + -3t2 = 2 + -2

Combine like terms: 2 + -2 = 0
-2 + 3t + -3t2 = 0

Begin completing the square.  Divide all terms by
-3 the coefficient of the squared term: 

Divide each side by '-3'.
0.6666666667 + -1t + t2 = 0

Move the constant term to the right:

Add '-0.6666666667' to each side of the equation.
0.6666666667 + -1t + -0.6666666667 + t2 = 0 + -0.6666666667

Reorder the terms:
0.6666666667 + -0.6666666667 + -1t + t2 = 0 + -0.6666666667

Combine like terms: 0.6666666667 + -0.6666666667 = 0.0000000000
0.0000000000 + -1t + t2 = 0 + -0.6666666667
-1t + t2 = 0 + -0.6666666667

Combine like terms: 0 + -0.6666666667 = -0.6666666667
-1t + t2 = -0.6666666667

The t term is -1t.  Take half its coefficient (-0.5).
Square it (0.25) and add it to both sides.

Add '0.25' to each side of the equation.
-1t + 0.25 + t2 = -0.6666666667 + 0.25

Reorder the terms:
0.25 + -1t + t2 = -0.6666666667 + 0.25

Combine like terms: -0.6666666667 + 0.25 = -0.4166666667
0.25 + -1t + t2 = -0.4166666667

Factor a perfect square on the left side:
(t + -0.5)(t + -0.5) = -0.4166666667

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| 3x+20=8x-30 | | 3u-3=3 | | 16t+3=67 | | 28x=21 | | -4a-3a=3-8a-2a | | X=20 | | 102x=17 | | 5t+8= | | 4.5x+6.5=-6.5 | | c=.55(59-32) | | -2y-8=6y+16 | | X=108 | | 7+4x=82 | | 9-r=2r+6 | | -23x=-161 | | 10u=0 | | 0=x^3-8x^2+15x | | 5+24t+-8t^2=0 | | 15w+21= | | 1-9x^2=0 | | x^2-x-272=0 | | x-(-56)=184 | | 4x+5=23x+1 | | x-56=184 | | 7+8=19 | | 2p+5q=7 | | 48-14= | | 4X+20=6X+9 | | x+x-14=82 | | -2-(-2)= | | 2x+3=12-x | | 4x+4=5x-14 |

Equations solver categories